Length and Timescales of Rift Faulting and Magma Intrusion: The Afar Rifting Cycle from 2005 to Present - Ebinger, C; Ayele, A; Keir, D; Rowland, J; Yirgu, G; Wright, T; Belachew, M; Hamling, I (Annual Review of Earth and Planetary Sciences, 2010)
Although fault and magmatic processes have achieved plate spreading at mid-ocean ridges throughout Earth’s history, discrete rifting episodes have rarely been observed. This paper synthesizes ongoing seismic, structural, space-based geodetic, and petrologic studies from the subaerial Red Sea rift in Ethiopia where a major rifting episode commenced in September 2005. Our aims are to determine the length and timescales of magmatism and faulting, the partitioning of strain between faulting and magmatism, and their implications for the maintenance of along-axis segmentation. Most of the magma for the initial and subsequent 12 intrusions was sourced from the center of the Dabbahu-Manda Hararo rift segment. Strain is accommodated primarily by axial dike intrusions fed from mid-segment magma chamber(s). These findings show that episodic (approximate century interval), rapid opening of discrete rift segments is the primary mechanism of plate boundary deformation. The scale (∼65 km × 8 km) and intensity of crustal deformation (∼6 m), as well as the volume of intrusive and extrusive magmatism (>3 km3), provokes a re-evaluation of seismic and volcanic hazards in subaerial rift zones.